Keith of the Border: A Tale of the Plains - Parrish, Randall, 1858-1923 (Salt Lake City, UT : Project Gutenberg, 2005)
"Keith of the Border: A Tale of the Plains" by Randall Parrish is a novel likely written in the late 19th century. This tale, set against the backdrop of the American West during a turbulent period marked by conflict between settlers and indigenous tribes, follows the adventures of Jack Keith, a seasoned plainsman navigating the dangers of the wilderness as he faces both human and natural threats. The opening portion introduces us to Jack Keith as he rides through the rugged terrain of the Western plains, showcasing his rugged appearance and hardened demeanor developed through years of frontier living. As he surveys the land, he becomes increasingly aware of the peril surrounding him due to rising tensions between settlers and various Indian tribes. When he stumbles upon the aftermath of an Indian raid that has resulted in tragedy, he is thrust into a web of intrigue, uncovering not only the grim fate of the victims but also the involvement of white men in the violence. This discovery sets him on a quest for vengeance and justice, establishing a gripping narrative that combines elements of adventure, mystery, and personal honor$1 (Ban engaging start that lays a robust foundation for Keith's ensuing journey. (This is an automatically generated summary.)s
Release date is 2005-02-01
Produced by Curtis A. Weyant, and David Widger
Keywords: Western stories; Love stories; Adventure stories; Frontier and pioneer life -- West (U.S.) -- Fiction; United States -- History -- Civil War, 1861-1865 -- Veterans -- Fiction